Analisis Perbandingan Kinerja Keuangan Bank Syariah Indonesia dan BCA Syariah Tahun 2021-2023 - Nurzianti, Rahma; Fitri Yunina (IHTIYATH : Jurnal Manajemen Keuangan Syariah, 2024)
This study aims to compare the financial performance of BSI and BCA Syariah in 2021-2023 using the Sharia Conformity and Profitability (SCnP) method. This research uses a descriptive quantitative approach and secondary data in the form of financial statements from BSI and BCA Syariah for the period 2021 to 2023. The results show that the comparison of the financial performance of BSI and BCA Syariah based on the SCnP method shows BSI's superiority in profitability, while BCA Syariah is superior in sharia compliance. Data and graphical analysis from 2021 to 2023 indicate that BSI's financial performance is in the Lower Right Quadrant (LRQ), while BCA Syariah during this period showed financial performance in the Upper Left Quadrant (ULQ). This research seeks to apply aspects of sharia compliance to Islamic banks through financial analysis. In addition, the recent transfer of priority customers from BSI to BCA Syariah is an important concern. Therefore, it is necessary to improve sharia compliance in all Islamic Commercial Banks. Indonesian Islamic banking can further develop, improve service quality, and maintain its sharia integrity, which in turn will strengthen its position in the domestic and international markets